Influence of Annealing on Creep Indentation, Surface Properties and Electrochemical Corrosion Behavior of Ni-Cr Based Dental Alloy - El-Bediwi, Abu Bakr; Kashita, Eman; Salman, Salah M.M. (International Journal of Applied Sciences and Biotechnology, 2017)
Heat treatment is a process in which alloy is heated to get different microstructures and desired properties associated with it which may affect the corrosion rate, nature form and size. Effect of annealing on microstructure, creep indentation, hardness and electrochemical corrosion behavior of Ni63Cr24.6Mo10.8Si1.5Mn0.06C0.04 alloy were investigated. Microstructure of Ni63Cr24.6Mo10.8Si1.5Mn0.06C0.04 alloy changed after annealing at different temperature for two hours. Crystal size of nickel in matrix alloy increased after annealing for two hours at different temperature. Stress exponent, n, Vickers hardness and calculated maximum shear stress of Ni63Cr24.6Mo10.8Si1.5Mn0.06C0.04 alloy decreased after annealing. Corrosion rate of Ni63Cr24.6Mo10.8Si1.5Mn0.06C0.04 alloy increased after annealing for two hours at different temperature. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 366-374